2004
DOI: 10.1063/1.1689758
|View full text |Cite
|
Sign up to set email alerts
|

The response of hydroxy-terminated polybutadiene to one-dimensional shock loading

Abstract: Hydroxy-terminated polybutadiene (HTPB) is commonly used as a binder system in rocket propellants and plastic bonded explosives (PBXs). As such, the investigation of this material under high-strain-rate and shock-loading conditions is of importance if the response of propellants and PBXs is to be understood. Therefore, the Hugoniot of two different HTPB compositions has been investigated, using manganin stress gauges. Both materials have a linear Us–up relationship, with the material having a higher plasticize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 18 publications
4
30
1
Order By: Relevance
“…However, other thermoplastics have been shocked and recovered [19] at stresses of up to 40 GPa, where no changes in the chemistry of the polymer were noted. We also noted no changes in recovered HTPB [5], when loaded up to more modest stresses of ca. 1.5 GPa.…”
Section: Article In Pressmentioning
confidence: 64%
See 1 more Smart Citation
“…However, other thermoplastics have been shocked and recovered [19] at stresses of up to 40 GPa, where no changes in the chemistry of the polymer were noted. We also noted no changes in recovered HTPB [5], when loaded up to more modest stresses of ca. 1.5 GPa.…”
Section: Article In Pressmentioning
confidence: 64%
“…This has included work on PBX binder systems such as Kel-F and estane [4] and hydroxy-terminated polybutadiene [5], and structural polymers such as polymethylmethacrylate (PMMA) [6], epoxy-based resins [7] and polytetrafluroethylene (PTFE-Teflon) [8,9]. One polymer that we have investigated in some depth is polyether ether ketone (PEEK) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium structure and dynamics of PBD have been the subjects of extensive experimental and theoretical study. [52][53][54][55][56][57][58][59][60][61][62] By contrast, there have been few fundamental studies on the shock response of PBD 36 and, to our knowledge, no detailed MD studies have been reported.…”
Section: Introductionmentioning
confidence: 95%
“…In one experiment, a composite consisting of 30 μm diameter glass beads in an HTPB matrix was impacted by a steel flyer plate traveling at 200 m s −1 [259]. In one experiment, a composite consisting of 30 μm diameter glass beads in an HTPB matrix was impacted by a steel flyer plate traveling at 200 m s −1 [259].…”
Section: Shock Recovery Of Polymersmentioning
confidence: 99%